2020
DOI: 10.1186/s12889-020-09852-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual factors associated with disposal of children’s stools in Papua New Guinea: evidence from the 2016–2018 demographic and health survey

Abstract: Background Proper sanitation has been one of the topmost priorities on the global public health agenda. In the past few decades, sanitation programs targeting households have often paid little attention to the disposal of children’s stools. We assessed the individual and contextual factors associated with disposal of children’s faeces in Papua New Guinea. Methods The data used for this study forms part of the 2016–2018 Papua New Guinea Demographic and Health Survey (PDHS). For this study, we focused on women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…The current study also showed that improved water supply was associated with safe child feces disposal which is in line with other studies in Guinea [ 23 ] and Nigeria [ 37 ]. Accessibility of improved water is a strategy to reduce the susceptibility of children to diarrhea and other poor sanitation-induced health conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The current study also showed that improved water supply was associated with safe child feces disposal which is in line with other studies in Guinea [ 23 ] and Nigeria [ 37 ]. Accessibility of improved water is a strategy to reduce the susceptibility of children to diarrhea and other poor sanitation-induced health conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike previous studies that found no association between mothers' education and safe disposal of child stools [20][21][22]49], this present study revealed that mothers without formal education were more likely to practise safe disposal. This finding seems counter-intuitive; however, the absence of formal education does not imply the absence of health education or knowledge on personal hygiene.…”
Section: Plos Onecontrasting
confidence: 99%
“…Azage & Haile 2015;Cronin et al 2016;Bawankule et al 2017;Islam et al 2018;Aliyu & Dahiru 2019;Sahiledengle 2019Sahiledengle , 2020Seidu et al 2020Seidu et al , 2021Simelane et al 2020;Getahun & Adane 2021;Soboksa 2021;Soboksa et al 2021;Vong et al 2021), while 6 studies were of moderate(Wilunda & Alessio 2009;Siruri 2013;Mihrete et al 2014;Aluko et al 2017;Sidabalok et al 2019;Alemayehu et al 2021) according to our assessment (Supplementary Material, Table…”
mentioning
confidence: 82%
“…Several studies done in Nepal (Lamichhane et al 2018), Indonesia (Cronin et al 2016), Thailand (Wilunda & Alessio 2009), Cambodia (Vong et al 2021), India (Bawankule et al 2017), and Kenya (World Bank/UNICEF 2015) have linked unsafe fecal disposal to an increased risk of childhood diarrhea. However, studies conducted in Ethiopia (Sahiledengle 2020), Papua New Guinea (Seidu et al 2020), Nigeria (Aluko et al 2017), and Eswatini (Simelane et al 2020) found that unsafe fecal disposal in children reduces the risk of childhood diarrhea. It might be that the availability of physical infrastructure alone is insufficient to assure the adoption of safe child feces disposal practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation